2022
DOI: 10.3389/fpsyg.2022.973676
|View full text |Cite
|
Sign up to set email alerts
|

Going green: Impact of green supply chain management practices on sustainability performance

Abstract: The rising environmental challenges are capturing the attention of stakeholders of corporations due to increasing competition. The sustainable performance of firms does not merely gauge their economic performance but also their sustainable development. Since the environmental supply chain management of firms has an important part in maneuvering their sustainable performance, the present study focuses on assessing the impact of green supply chain management practices on the sustainable performance of the textil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 55 publications
(74 reference statements)
0
16
0
Order By: Relevance
“…2.8 Green supply chain practices and sustainability GSCP state that the firm's SC activities are environmentally friendly (Ahmad et al, 2022); these activities initiated by generating ideas and growing through sustainable product designs, green logistics, green purchasing, green manufacturing and managing all types of wastage through green conception have a significant impact on sustainable performance (Chen et al, 2021;Gao et al, 2009;Green et al, 2012;Miao et al, 2022;Owusu et al, 2021;Sun et al, 2021;Yang et al, 2022). Earlier studies indicated a positive role of GSCP for sustainability (Awan et al, 2017), including social, economic and environmental performance aspects (Muhammad et al, 2020).…”
Section: Green Human Resource Management and Sustainabilitymentioning
confidence: 99%
“…2.8 Green supply chain practices and sustainability GSCP state that the firm's SC activities are environmentally friendly (Ahmad et al, 2022); these activities initiated by generating ideas and growing through sustainable product designs, green logistics, green purchasing, green manufacturing and managing all types of wastage through green conception have a significant impact on sustainable performance (Chen et al, 2021;Gao et al, 2009;Green et al, 2012;Miao et al, 2022;Owusu et al, 2021;Sun et al, 2021;Yang et al, 2022). Earlier studies indicated a positive role of GSCP for sustainability (Awan et al, 2017), including social, economic and environmental performance aspects (Muhammad et al, 2020).…”
Section: Green Human Resource Management and Sustainabilitymentioning
confidence: 99%
“…Green innovation has become one of the mostimportantapproachestoachievingsustainabledevelopment in modern life. 2 Environmental regulation largely impacts green technology innovation. Healthcare delivery has been recognized as a major area of opportunity for decarbonizing health care, an area where there is enormous potential to develop zero_carbon 'digitally-enabled,patient-centredcare'.…”
Section: Introductionmentioning
confidence: 99%
“…3 Asforany disease,'goinggreen'includes(i)theimprovement,design,orconstructionofhealthcarefacilities;(ii)dailyoperationssuchascleaning, maintenance, and many clinical functions; and (iii) purchasing, foodandtransportation. 2,4 Becominggreenineachoftheseareas canpotentiallyimprovehealthcare,anddirectlyandindirectlybenefitpatienthealth.Moreover,therearespecificactionstargetedat patients with allergic diseases, such as those related to the use of inhaledmedication.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations